Two decades of post-socialism in Serbia: Lessons learned and emerging issues in human resource management - Biljana Bogicevic Milikic; Nebojsa Janicijevic; Bozidar Cerovic (Journal for East European Management Studies, 2012)
The success and speed of transition processes in post-socialist countries produced quite different results regarding theirs institutional and economic systems. As far as Human Resources Management (HRM) practices are concerned, the main challenge for managers in these countries seem to be how to efficiently replicate HRM practices from the Western capitalistic countries, taking into account the fact that there are considerable differences in institutional, cultural and economic contexts. A few available empirical studies from Serbia revealed mixed findings suggesting that there are evident signs of both forces - the convergence and the divergence of HRM practices in Serbia compared to the Western ones. The aim of this paper, therefore, is to investigate HRM practices in Serbia, in order to shed light on some emerging issues in HRM, which may be of significance regards further studies. – – Der Erfolg und die Geschwindigkeit von Übergangsprozessen in ehemals sozialistischen Ländern produzieren relativ unterschiedliche Ergebnisse im Hinblick auf ihr institutionelles und wirtschaftliches System. Bezüglich der HRMPraktiken scheint die größte Herausforderung für Manager in diesen Ländern zu sein, wie man effizient HRM-Praktiken aus westlichen Ländern, unter Berücksichtigung der unterschiedlichen institutionellen, wirtschaftlichen und kulturellen Kontexte, anwenden kann. Einige verfügbare Studien aus Serbien ergaben unterschiedliche Ergebnisse im Bezug auf die Existenz von beiden Kräften - Konvergenz und Divergenz - der HRM-Praktiken in Serbien im Vergleich zu westlichen Ländern. Das Ziel dieses Artikels ist, HRM-Praktiken in Serbien zu untersuchen, um einige weitere Fragen der HRM zu beleuchten, die möglicherweise von großer Bedeutung für weitere Studien sein könnten.
Keywords: 650; transition; human resource management practices; crossvergence; transvergence